The Role of Islamic Education in Shaping a Generation of Character - Dede Arif Rahman Nurhakim; Opik Taupik Kurahman; Dadan Rusmana (LECTURES: Journal of Islamic and Education Studies, 2025)
Islamic education integrates Islamic values into learning, focusing on the development of good character. This significantly contributes to the creation of a young generation that excels academically while possessing a strong personality in terms of ethics, spirituality, and social life. Based on literature review, it was found that the application of Qur'anic values and the Prophet's Sunnah in the educational process can serve as a solid foundation in producing individuals who are faithful, devout, and capable of making positive contributions to society. Thus, Islamic education aims not only to create a generation that excels in knowledge but also one that can implement Islamic values in everyday life and benefit their surroundings.